Monitoring of microbiological dynamics in beach sand and seawater samples from recreational and non-recreational beaches over a two-year period - Sanliturk, Gizem; Guran, Mumtaz (Taylor & Francis Ltd, 2022)
The frequencies of Escherichia coli, Staphylococcus aureus and Methicillin-resistant S. aureus (MRSA) and 'aerobic mesophilic bacteria' (AMB) counts in different seasons and marine sources were compared to understand the microbiological dynamics at beaches in N. Cyprus. Also, antibiotic resistance patterns were evaluated. The characterization and AMB enumeration studies were performed by conventional microbiological methods. AMB counts increased from winter to summer significantly (45.5*10(4) CFU/mL to 2.5*10(6) CFU/mL). Similarly, percentage detection frequencies of the bacteria were higher in summer compared to winter and were significant particularly for E. coli in both sand and seawater samples in 2019 and 2020 (p = 0.0181, p = 0.0142, p = 0.1257, p = 0.0446, respectively). However, a significant difference was not detected in percentage detection frequencies in terms of different sources or recreational status of beaches. The highest resistance percentages were detected against beta-lactam and lincosamides group of antibiotics. Results of the study signified that regular microbiological monitoring for beaches is essential.
Keywords: Sand; seawater; s; aureus; mrsa; e; coli; antibiotic resistance